TEACHER EDUCATION: AN IMPERATIVE FOR NIGERIA’S VISION 2020 - Mohammed, A F; Adeniyi, Adeshina E; Uyagu, Grace; Yahaya, Buhari; Mohammed, Risikatu (Sokoto Educational Review, 2017)
The major focus of this paper is an examination of how teacher education can be used to respond to the Nigeria vision 2020 challenges which entails total development plan for the nation. More specifically, the paper examined how teacher education could partly helped in attaining the goal of vision 2020 in making the country economically prosperous, politically stable and socially harmonious. To achieve these objectives, the paper examined the concepts of national development, teacher education, its objectives and curricular and relate them to the issues of vision 2020. The paper suggested the need for teacher education programme to be improved upon within the context of vision 2020.